First report of unusual case of parasitism by Amblyomma nodosum (Neumann, 1889) in a yellow cururu toad (Rhinella icterica) in the Northeastern Brazilian Caatinga - Lee, Daniel Antônio Braga [UNESP]; Barros-Battesti, Darci Moraes [UNESP]; Arantes, Paulo Vitor Cadina [UNESP]; Sada, Jovêncio Mateus [UNESP]; Sanches, Gustavo Seron [UNESP]; André, Marcos Rogério [UNESP]; Lima, Victor Fernando Santana (FapUNIFESP (SciELO), 2024)
The Amblyomma genus (Arachnida: Ixodidae) is widely distributed in South America, with 34 species occurring in Brazil. Amblyomma nodosum Neumann 1889 is a species that predominantly feeds on Passeriformes during immature stages (larvae and nymphs) and anteaters (Myrmecophagidae) during adult stages. The aim of the present study is to report, for the first time, an unusual case of parasitism by adults of A. nodosum on a yellow cururu toad (Rhinella icterica) captured in the city of Nossa Senhora da Glória, Sergipe state (Northeastern Brazil) in the Caatinga biome, and also investigate the presence of DNA of Rickettsia in the collected material. DNA was extracted from all specimens collected (N=8) and subjected to PCR assays based on the tick 16S rRNA endogenous gene and gltA gene for Rickettsia sp. All samples (8/8; 100%) were positive for the 16S rRNA endogenous gene and two amplicons (obtained from one male and one female) were purified and sequenced. The BLASTn analysis of the sequences revealed a high degree of similarity (95-100%) with A. nodosum sequences previously deposited on GenBank, while the phylogenetic analysis clustered the sequences obtained in the same clade as A. nodosum sequences from Brazil.
Primeiro relato de caso de parasitismo incomum por Amblyomma nodosum (Neumann, 1889) em um sapo-cururu (Rhinella icterica) na Caatinga, nordeste Brasileiro
Keywords: Amblyomma nodosum; amphibian; host; Tick